2015
DOI: 10.18579/jpcrkc/2015/14/2/79075
|View full text |Cite
|
Sign up to set email alerts
|

Stock Status Assessment of Health Commodities Used in the Management of HIV/AIDS and Tuberculosis in Kano State, Nigeria

Abstract: Purpose-The objective of this research is to assess stock of health commodities used in the management of HIV/AIDS and tuberculosis in Kano State, Nigeria. This assessment will reveal the sum of stock levels available at the state warehouse and health facilities, then determining for how long they can last. Approach-Data from Logistics Management Information System (LMIS) tools for the last quarter of year 2014 were obtained and information on 'stock on hand' and 'average monthly consumption' were extracted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…In support of this finding, a research done in Namibia, Nigeria, and in sub-Saharan Africa shows that inadequate warehouse infrastructure (storage capacity) and inadequate warehouse management (lack of expertise of human resources and insufficient operational processes) are some of the challenges for good storage practice. 26,30,31 The present study has also shown that storage guidelines have an association with good storage practice. In line with this, guidelines for improving performance of logistic management systems which are developed by USAID/DELIVER identified that storage guidelines are a factor that affects good storage practice results in lack of consistency in practice and non-accountability of staff.…”
Section: Storage Conditionsupporting
confidence: 63%
See 1 more Smart Citation
“…In support of this finding, a research done in Namibia, Nigeria, and in sub-Saharan Africa shows that inadequate warehouse infrastructure (storage capacity) and inadequate warehouse management (lack of expertise of human resources and insufficient operational processes) are some of the challenges for good storage practice. 26,30,31 The present study has also shown that storage guidelines have an association with good storage practice. In line with this, guidelines for improving performance of logistic management systems which are developed by USAID/DELIVER identified that storage guidelines are a factor that affects good storage practice results in lack of consistency in practice and non-accountability of staff.…”
Section: Storage Conditionsupporting
confidence: 63%
“…In the other way, this research finding showed that none of the HF was stocked out for RHZE/RH kit for the past 6 months which was in line with research done in East Shewa, Oromia region. 25 But it was lower than a study done in Nigeria (19.7%) 30 and Tanzania (21%). 33 This difference may be due to TB kit implementation which was newly introduced in Ethiopia as compared to Nigeria in which more attention is given for the kit implementation, whereas Tanzania does not implement TB kit at the time of survey.…”
Section: Discussionmentioning
confidence: 74%
“…The present study revealed an 80% facility reporting rate. This finding was lower than the study conducted in Kano state, Nigeria (84%) and East Wollega zone, Ethiopia (97%) (29,37). This difference might be due to improved utilization of report and requisition forms in the health facilities of the former study and the product type under investigation which was program drugs in the previous study.…”
Section: Discussioncontrasting
confidence: 63%
“…So far, studies that assessed public health commodity management in Nigeria focused on a few states and did not cover the full breadth of the SCM functions. [14][15][16][17] Additionally, there is no recent study on the availability of under-5 malaria commodities within the Nigeria public health system.…”
mentioning
confidence: 99%